The Inter-Agency Coordination and Electoral Data Integrity: A Governance Perspective from Bengkulu - Rio Putra Handika; Syahidallazi Aziz; Sondang Amelia Hasibuan; Harry Yanza Putra; Heru Purnawan (Pencerah, 2026)
This study analyzes the coordination between the Provincial Office of Population and Civil Registration (Disdukcapil) and the Bengkulu Provincial General Election Commission (KPU) in synchronizing voter data for the 2019 General Election. The research aims to examine the forms and effectiveness of inter-institutional coordination in ensuring the accuracy and reliability of voter data to support electoral implementation. A qualitative approach with a descriptive method was employed. Data were collected through in-depth interviews and a systematic review of official documents related to the 2019 election in Bengkulu Province. The analysis focuses on the role of both institutions as problem-solving actors in addressing technical and administrative challenges, including duplicate voter records, inconsistencies between domicile data and voter allocation, and other data-related discrepancies. The findings reveal that coordination was conducted through formal coordination meetings, plenary sessions, inter-agency communication, data consolidation, matching processes, as well as field verification and validation activities, supported by joint decision-making mechanisms. These efforts contributed to improving data accuracy and administrative efficiency. However, the study also identifies persistent challenges, indicating that coordination and data management practices require further optimization to achieve more effective electoral governance.